The acceptance of solar water pump technology among rural farmers of northern Pakistan: A structural equation model - Deyi Zhou; Abdullah (Cogent Food & Agriculture, 2017)
The situation of electricity is deteriorating in Pakistan and load shedding prevails in all parts of the country which not only affect the general life but also leads to lower agricultural productivity in rural areas. The purpose of this study is to explore the factors that influence the acceptance of solar water pump (SWP) technology. For this purpose, a SWP technology acceptance model was proposed based on technology acceptance model (TAM) and unified theory of acceptance and use of technology. Six variables were used to assess the model which includes; perceived usefulness, perceived ease of use, facilitating conditions (FC), cost tolerance (CT), awareness and attitude towards SWP usage. Data were collected from 450 rural farmers employing structured questionnaire through face to face interviews. The questions were orally translated to farmers due to lack of education. The method of structural equation modeling was used to test and confirm the hypothesized model. Results indicated that out of eight hypotheses, seven were supported while one was not supported. Moreover, the results show that better predictors of SWP technology usage were gender, age, education awareness, CT, FC, ease of use and usefulness. The study is valuable as it applied TAM to study the factors influencing the acceptance of SWP technology for the first time in the context of Pakistan.